The Role and Function of Ethnology in Developing the Aesthetic Competence: A Case Study on Philology Students - Snikhovska, Irena; Glazunova, Lesya; Soloviova, Larysa; Tymchuk, Olena (Journal of History Culture and Art Research, 2021)
The article is devoted to the experimental testing of aesthetic competence of future philologists by means of ethnology. The principles (national character, humanization, ethnicization, cultural conformity, integration) are considered and stages of model implementation (orientative, training, creative) are elaborated and characterized. Structural and functional components, criteria and indicators of the levels of forming the future philologists’ aesthetic competence are defined. The characteristic of levels of aesthetic competence development in philology students (reproductive, constructive, creative) is given. The characteristics of the levels with the help of the coefficient of tasks completeness related to knowledge, skills and abilities for aesthetic competence development of the philology students by means of ethnology were determined. The paper concludes by calling attention to the enhancement of the educational process forms and methods in order to develop the aesthetic competence of future philologists by means of ethnology, urging to instill the aesthetic competences more purposefully and integrally throughout the Bachelor program.